Small active and sterile neutrino masses from the TeV scale - Perez-Lorenzana, A.; Pires, CAD (Elsevier B.V., 2001)
A new mechanism for understanding small neutrino masses using only simple new physics at the TeV scale is proposed. As an application, it is shown how it can naturally lead to the mass hierarchy of the so-called bimaximal mixing in the case of three active neutrinos, or to the 3 + 1 scenario with a sterile neutrino, using only the SU(2)(L) quantum numbers of the particles. (C) 2001 Elsevier B.V. BN. All rights reserved.